2005
DOI: 10.1007/s00213-005-0199-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cannabinoid CB1 receptor antagonist SR-141716A on ethanol self-administration and ethanol-seeking behaviour in rats

Abstract: Results emphasize that endocannabinoid mechanisms play a major role in the control of ethanol self-administration and in the reinstatement of conditioned ethanol seeking. However, these effects extend to the control of operant behaviours motivated by natural rewards (i.e. sucrose). On the other hand, SR-141716A only weakly reduces NaCl self-administration in sodium-depleted rats, in which salt intake is largely controlled by homeostatic mechanisms. Overall, these observations demonstrate that the inhibition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
109
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(127 citation statements)
references
References 61 publications
16
109
1
1
Order By: Relevance
“…Our results support a key recent finding that blockade of the CB1 receptor system can also suppress conditioned seeking for palatable foods Economidou et al, 2006). In the present study, 1.0 mg/ kg SR141716A was sufficient to attenuate cue-induced reinstatement of Ensure s seeking in mice, and demonstrated that this dose also decreased reinstatement of sucrose seeking in rats.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results support a key recent finding that blockade of the CB1 receptor system can also suppress conditioned seeking for palatable foods Economidou et al, 2006). In the present study, 1.0 mg/ kg SR141716A was sufficient to attenuate cue-induced reinstatement of Ensure s seeking in mice, and demonstrated that this dose also decreased reinstatement of sucrose seeking in rats.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that SR141716A reliably and potently attenuates cue-induced reinstatement for several drugs of abuse in rats, for example heroin, nicotine (1.0 mg/kg; De Vries et al, 2003, 2005, ethanol, and cocaine (0.3 mg/kg; Economidou et al, 2006;De Vries et al, 2001). Our results support a key recent finding that blockade of the CB1 receptor system can also suppress conditioned seeking for palatable foods Economidou et al, 2006).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Furthermore, several reports suggest that blockade of the CB 1 -R decreases the intake of ethanol drinking in different animal models (Rodriguez de Fonseca et al, 1999;Lallemand et al, 2001Lallemand et al, , 2004Cippitelli et al, 2005;Colombo et al, 2005;Gessa et al, 2005;Economidou et al, 2006). The results of this study revealed that a 4-week consumption of ethanol increased CB 1 -R in CPu, VMN, and DG of the hippocampus.…”
Section: Discussionsupporting
confidence: 60%
“…Auditory and visual stimuli were presented through a speaker and a light located on the front panel. Rats were trained to selfadminister 10% alcohol (v/v) in 30-min daily sessions on a fixed-ratio 1 schedule of reinforcement, in which each response resulted in delivery of 0.1 ml of fluid, as described earlier (Economidou et al, 2006). In all the experiments, the number of operant responses at both the active and the inactive levers was recorded.…”
Section: Operant Training and Ethanol Self-administrationmentioning
confidence: 99%